2012
DOI: 10.1103/physrevb.86.075444
|View full text |Cite
|
Sign up to set email alerts
|

Interlayer commensurability and superlubricity in rigid layered materials

Abstract: Superlubricity is a frictionless tribological state sometimes occurring in nanoscale material junctions. It is often associated with incommensurate surface lattice structures appearing at the interface. Here, by using the recently introduced registry index concept which quantifies the registry mismatch in layered materials, we prove the existence of a direct relation between interlayer commensurability and wearless friction in layered materials. We show that our simple and intuitive model is able to capture, d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
68
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(71 citation statements)
references
References 103 publications
3
68
0
Order By: Relevance
“…This is consistent with the previous studies on superlubricity in graphite or graphene [6,13,14,17,18,20,22] which showed that superlubricity may occur in incommensurate contacts. However, for a very soft substrate (e.g., with a support stiffness of k=0.05 nN/nm, nearly suspended),…”
Section: Nn/atomsupporting
confidence: 93%
See 2 more Smart Citations
“…This is consistent with the previous studies on superlubricity in graphite or graphene [6,13,14,17,18,20,22] which showed that superlubricity may occur in incommensurate contacts. However, for a very soft substrate (e.g., with a support stiffness of k=0.05 nN/nm, nearly suspended),…”
Section: Nn/atomsupporting
confidence: 93%
“…This means that a soft substrate (e.g., with a support stiffness less than 0.05 nN/nm) may impede superlubricity, further indicating that, besides the commensurability [13,14,18,20,22,23], normal load [21], flake size [18,21], etc., the stiffness too is a dominant parameter for superlubricity. The physical mechanism of the friction in the commensurate case higher than that in the incommensurate case is correlated with the stick-slip behavior of the flake on the substrate.…”
Section: Nn/atommentioning
confidence: 96%
See 1 more Smart Citation
“…In turn, the result is high static friction and stick-slip behaviour, resulting in high dynamical friction. 41 However, if the egg boxes are rotated relative to one another, yielding an incommensurate state, all unit cells now only have to cross a much smaller barrier at any point along the sliding path, i.e., we expect reduced resistance towards shear/sliding. Whereas we are overcoming obvious physical barriers when sliding egg boxes over one another, for (atomically smooth) lamellar materials the energetic barriers are caused by enhanced Pauli repulsions between the overlapping electron clouds as they encounter each other during the sliding process.…”
mentioning
confidence: 99%
“…Hirano further suggested in 2014 [15] that the superlubricity occurs only at the frictional contact between two crystals. However, since the publication of Superlubricity [16] by Martin and Erdemir in 2007, in which superlubricity was defined as having a friction coefficient smaller than 0.01, many DLC researchers, including those mentioned above, have adopted Martin's definition for developments in carbon films in which a friction coefficient smaller than 0.01 is frequently attained [8,[17][18][19].…”
Section: Introductionmentioning
confidence: 99%